The Peruvian Experience in the Liberalization of Telecommunication Servicies: interconnection issues - Organismo Supervisor de Inversión Privada en Telecomunicaciones (Perú) (2000)
Interconnection is a set of agreements and rules which main objective is to allow the communication of users of different networks. The concept of interconnection involves physical aspects as well as the interoperability of services. Interconnection is an obligation, this includes an open access to the network, its infrastructure and services.